2011
DOI: 10.4028/www.scientific.net/kem.462-463.1
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Behavior of 2D C/SiC Composites at Elevated Temperatures under Uniaxial Compression

Abstract: As Carbon-fiber-reinforced SiC-matrix (C/SiC) composites are widely used in high-temperature structural applications, its mechanical behavior at high temperature is important for the reliability of structures. In this paper, mechanical behavior of a kind of 2D C/SiC composite was investigated at temperatures ranging from room temperature (20C) to 600C under quasi-static and dynamic uniaxial compression. The results show the composite has excellent high temperature mechanical properties at the tested temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…From which it can be seen that D basically equals zero when the stress is less than 80MPa and the composite is in the first segment of elasticity, thus no damage can be observed from the figure 5 (a)-(c); later when the stress value increases from 80MPa to 150MPa and enters the second stage of yielding, the composite is being damaged with a very small damage (D less than 0.1), thus small cracks and regional fiber yielding can be observed on the surface of the specimen ( due to the influence of temperature elevation on the dynamic tensile property of 2D C/SiC composites [27]. At 173K, the tensile strength reaches maximum value of 335MPa and 307MPa for coated and uncoated specimen, up by 18% and 15% than that of 293K, and slightly lower in failure strain than that of 293K.…”
Section: Impact Damagementioning
confidence: 97%
See 1 more Smart Citation
“…From which it can be seen that D basically equals zero when the stress is less than 80MPa and the composite is in the first segment of elasticity, thus no damage can be observed from the figure 5 (a)-(c); later when the stress value increases from 80MPa to 150MPa and enters the second stage of yielding, the composite is being damaged with a very small damage (D less than 0.1), thus small cracks and regional fiber yielding can be observed on the surface of the specimen ( due to the influence of temperature elevation on the dynamic tensile property of 2D C/SiC composites [27]. At 173K, the tensile strength reaches maximum value of 335MPa and 307MPa for coated and uncoated specimen, up by 18% and 15% than that of 293K, and slightly lower in failure strain than that of 293K.…”
Section: Impact Damagementioning
confidence: 97%
“…Labrugere [24,25] et al studied the dynamic tensile properties of the material at 1100-1300 which turned out to be supreme. Li et al [26][27][28] systematically investigated into the dynamic compressive properties of C/SiC material at strain rates ranging from quasi-static to 10 3 /s and temperatures ranging from room temperature to 1273K. The results showed that the material is strain-rate sensitive with the dynamic compressive strength decreased with the increase of rise of temperature.…”
mentioning
confidence: 99%
“…Compared with CVI and LSI, PIP has many advantages such as lower component fabrication time to reduce costs significantly and lower fabrication temperature [6,7]. Compression is an important load state of C/SiC materials in service [8,9]. Moreover, the C/SiC components will fail due to the compression damage even when the components are loaded in tension [10].…”
Section: Introductionmentioning
confidence: 99%